2022
DOI: 10.1186/s12974-022-02645-1
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal microRNA-26a-3p deficit contributes to neuroinflammation and behavioral disorders via p38 MAPK signaling pathway in rats

Abstract: Background Neuronal injury is considered a critical risk factor in the pathogenesis of most neurological and neuropsychiatric diseases. However, the underlying molecular mechanisms and identification of potential therapeutic targets for preventing neuronal injury associated with brain function remain largely uncharacterized. Therefore, identifying neural mechanisms would put new insights into the progression of this condition and provide novel therapeutic strategies for the treatment of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, studies have indicated that miR-26a-3p can enhance autophagosome/lysosomal activity, facilitate synaptic plasticity, and repress neuronal cell apoptosis [13]. Moreover, miR-26a-3p absence results in an elevation in the expressions of pro-inflammatory factors IL-6β, IL-4, and TNF-α in the injured neurons [14]. Our results discovered that miR-26a-3p expression in BMSCs was reduced via the exosome inhibitor GW4869.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition, studies have indicated that miR-26a-3p can enhance autophagosome/lysosomal activity, facilitate synaptic plasticity, and repress neuronal cell apoptosis [13]. Moreover, miR-26a-3p absence results in an elevation in the expressions of pro-inflammatory factors IL-6β, IL-4, and TNF-α in the injured neurons [14]. Our results discovered that miR-26a-3p expression in BMSCs was reduced via the exosome inhibitor GW4869.…”
Section: Discussionmentioning
confidence: 56%
“…MiR-26a-3p is closely related to synaptic formation and plasticity in the nervous system. The involvement and modulation of miR-26a-3p have been found in neurological diseases and some cancers [13,14,32]. In addition, studies have indicated that miR-26a-3p can enhance autophagosome/lysosomal activity, facilitate synaptic plasticity, and repress neuronal cell apoptosis [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK and JNK were unchanged after chronic stress or CGA treatment. p38MAPK is an important member of MAPK, which is not only involved in the cell cycle, development, differentiation, cell death, senescence, and tumorigenesis, but also acts as a specific serine/threonine kinase to regulate inflammation. , A large number of studies have shown that p38 could activate the NF-κB signaling pathway, thereby causing inflammation in some diseases such as IBD, alcohol-induced hepatic injury, lung inflammation, and Parkinson’s. After SB203580 intervention, the phosphorylation level of p65 was significantly reduced, and the transcription and translation levels of TNF were significantly reduced. The intestinal damage was also significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…As a prominent intracellular signaling pathway, the MAPK pathway is of great importance in several critical physiological processes, including learning, memory, development, and cell differentiation [ 37 , 38 ]. The MAPK cascade is required for spatial and contextual learning in mice and is associated with hippocampal neurodegeneration [ 39 , 40 ]. It is noteworthy that Notch signaling pathways exhibited a correlation with both hyper- and hypomethylation of distinct genes (Fig.…”
Section: Discussionmentioning
confidence: 99%